2002
DOI: 10.1248/cpb.50.665
|View full text |Cite
|
Sign up to set email alerts
|

New Phenylethanoid Glycosides from Veronica pectinata var. glandulosa and Their Free Radical Scavenging Activities.

Abstract: In the flora of Turkey, genus Veronica L. (Scrophulariaceae) is represented by 79 species, 26 of which are endemic.1) Some of the Veronica species are used as diuretics and for wound healing in traditional Turkish medicine.2) Several Veronica species are used for the treatment of cancer, influenza, hemoptysis, laryngopharyngitis, hernia, and against cough, and respiratory diseases plus as an expectorant and antiscorbutic in different countries.3-5) Veronica species contain mainly iridoid glucosides, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…cuneifolia and V. cymbalaria hemoptysis, laryngopharyngitis, hernia, cough, and respiratory diseases, and are also used as an expectorant and antiscorbutic (Tomassini et al, 1995;Su et al, 1999;Grahamet et al, 2000). Earlier investigations performed on Veronica species resulted in the isolation mainly of iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid, and flavonoid glycosides (Chari et al, 1981;Taskova et al, 1998;Harput et al, 2002aHarput et al, , 2002bSaracoglu et al, 2002;Jensen et al, 2005). In this study, Veronica cuneifolia subsp.…”
Section: Research Articlementioning
confidence: 82%
“…cuneifolia and V. cymbalaria hemoptysis, laryngopharyngitis, hernia, cough, and respiratory diseases, and are also used as an expectorant and antiscorbutic (Tomassini et al, 1995;Su et al, 1999;Grahamet et al, 2000). Earlier investigations performed on Veronica species resulted in the isolation mainly of iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid, and flavonoid glycosides (Chari et al, 1981;Taskova et al, 1998;Harput et al, 2002aHarput et al, , 2002bSaracoglu et al, 2002;Jensen et al, 2005). In this study, Veronica cuneifolia subsp.…”
Section: Research Articlementioning
confidence: 82%
“…In our previous studies on Veronica species, we have reported that the antioxidant, anti-inflammatory and cytotoxic activities of the plant extracts and the isolated compounds (Harput et al, 2002b,c;Saracoglu et al, 2002). On the basis of these results we determined the free radical scavenging activity of isolated compounds (1-9) using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) free radical scavenging system by comparing 3-tert-butyl-4-hydroxy-anisole (BHA), widely used synthetic antioxidant and dl-a-tocopherol (a-TOC), commonly used natural antioxidant.…”
Section: Resultsmentioning
confidence: 98%
“…The free radical scavenging effect of the isolated compounds 1-9 was assessed by the decoloration of ethanol solution of DPPH spectroscopically; BHA and dl-a-tocopherol were used as standards (Table 2) (Hatano et al, 1989;Harput et al, 2002b,c;Saracoglu et al, 2002). Each EtOH solution (100 ll) of compounds 1-9 at various concentrations (10-0.1 lM) was added to 1.5 Â 10 À5 M DPPH/EtOH solution.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…All the analyses were done in triplicate. [17][18][19][20] SO radical-scavenging activity by alkaline dimethyl sulfoxide (DMSO) method. The method of Elizabeth and Rao 21 was used to detect SO radical-scavenging activity of the extract, with slight modification.…”
mentioning
confidence: 99%